Comparing classification methods for diffuse reflectance spectra to improve tissue specific laser surgery - Engelhardt, Albrecht; Kanawade, Rajesh; Knipfer, Christian; Schmid, Matthias; Stelzle, Florian; Adler, Werner (Bmc Medical Research Methodology, 2014)
In the field of oral and maxillofacial surgery, newly developed laser scalpels have multiple advantages over traditional metal scalpels. However, they lack haptic feedback. This is dangerous near e.g. nerve tissue, which has to be preserved during surgery. One solution to this problem is to train an algorithm that analyzes the reflected light spectra during surgery and can classify these spectra into different tissue types, in order to ultimately send a warning or temporarily switch off the laser when critical tissue is about to be ablated. Various machine learning algorithms are available for this task, but a detailed analysis is needed to assess the most appropriate algorithm.In this study, a small data set is used to simulate many larger data sets according to a multivariate Gaussian distribution. Various machine learning algorithms are then trained and evaluated on these data sets. The algorithms' performance is subsequently evaluated and compared by averaged confusion matrices and ultimately by boxplots of misclassification rates. The results are validated on the smaller, experimental data set.Most classifiers have a median misclassification rate below 0.25 in the simulated data. The most notable performance was observed for the Penalized Discriminant Analysis, with a misclassifiaction rate of 0.00 in the simulated data, and an average misclassification rate of 0.02 in a 10-fold cross validation on the original data.The results suggest a Penalized Discriminant Analysis is the most promising approach, most probably because it considers the functional, correlated nature of the reflectance spectra.The results of this study improve the accuracy of real-time tissue discrimination and are an essential step towards improving the safety of oral laser surgery.
EVALuna2:5453

Dependence of the capillary/vessel spatial pattern estimated by measuring diffuse reflectance spectra on the hemoglobin concentration level - Kanawade, Rajesh; Häußermann, Johannes; Klämpfl, Florian; Schmidt, Michael; Stelzle, Florian (Asia Communications and Photonics Conference, ACP, 2013)
The goal of this research is to study the behavior of the blood vessel density/spatial pattern estimated by measuring diffuce reflectance spectra depending on hemoglobin concentrations level for the application of early sign of the clinical shock detection. © OSA 2013.
CRIS-Team Scopus Importer:2023-03-07

Extension of depth-resolved reconstruction of attenuation coefficients in optical coherence tomography for slim samples - Hohmann, Martin; Lengenfelder, Benjamin; Kanawade, Rajesh; Klämpfl, Florian; Schmidt, Michael (Optical Coherence Tomography 2, 2015)
Coherent light propagating through turbid media is attenuated due to scattering and absorption. The decrease of the intensity of the coherent light is described by the attenuation coefficient. The measured decay of the coherent light through turbid media with optical coherence tomography (OCT) can be used to reconstruct the attenuation coefficient. Since most of the OCT systems work in the near-infrared region, they are the optical window from 800-1400 nm in tissue. Hence, the most part of the attenuation coefficient is caused due to the scattering. Therefore, deriving the attenuation coefficient is one way to get an approximation of the scattering coefficient which is difficult to access even up to day. Moreover, OCT measurements are one of the few possibilities to derive physical properties with micrometre resolution of the media under investigation.
Keywords: OCT; Optical Coherence Tomography; attenuation coefficent; reconstruction

Improved cancer diagnostics by different image processing techniques on OCT images - Kanawade, Rajesh; Lengenfelder, Benjamin; Menezes, Tassiana Marini; Hohmann, Martin; Kopfinger, Stefan; Hohmann, Tim; Grabiec, Urszula; Klämpfl, Florian; Menezes, Jean Gonzales; Waldner, Maximilian; Schmidt, Michael (Proceedings of SPIE, 2015)
Optical-coherence tomography (OCT) is a promising non-invasive, high-resolution imaging modality which can be used for cancer diagnosis and its therapeutic assessment. However, speckle noise makes detection of cancer boundaries and image segmentation problematic and unreliable. Therefore, to improve the image analysis for a precise cancer border detection, the performance of different image processing algorithms such as mean, median, hybrid median filter and rotational kernel transformation (RKT) for this task is investigated. This is done on OCT images acquired from an ex-vivo human cancerous mucosa and in vitro by using cultivated tumour applied on organotypical hippocampal slice cultures. The preliminary results confirm that the border between the healthy and the cancer lesions can be identified precisely. The obtained results are verified with fluorescence microscopy. This research can improve cancer diagnosis and the detection of borders between healthy and cancerous tissue. Thus, it could also reduce the number of biopsies required during screening endoscopy by providing better guidance to the physician.

Investigation of Laser Induced Breakdown Spectroscopy (LIBS) for the Differentiation of Nerve and Gland Tissue—A Possible Application for a Laser Surgery Feedback Control Mechanism - Mehari, Fanuel; Rohde, Maximilian; Knipfer, Christian; Kanawade, Rajesh; Klämpfl, Florian; Adler, Werner; Oetter, Nico; Stelzle, Florian; Schmidt, Michael (Plasma Science & Technology, 2016)
Laser surgery provides clean, fast and accurate modeling of tissue. However, the inability to determine what kind of tissue is being ablated at the bottom of the cut may lead to the iatrogenic damage of structures that were meant to be preserved. In this context, nerve preservation is one of the key challenges in any surgical procedure. One example is the treatment of parotid gland pathologies, where the facial nerve (N. VII) and its main branches run through and fan out inside the glands parenchyma. A feedback system that automatically stops the ablation to prevent nerve-tissue damage could greatly increase the applicability and safety of surgical laser systems. In the present study, Laser Induced Breakdown Spectroscopy (LIBS) is used to differentiate between nerve and gland tissue of an <i style="margin: 0px; padding: 0px; border: 0px; font-stretch: inherit; font-size: 16px; line-height: 25.6px; font-family: Georgia, "Times New Roman", STIXGeneral, serif; vertical-align: baseline; color: rgb(51, 51, 51);">ex-vivo pig animal model. The LIBS results obtained in this preliminary experiment suggest that the measured spectra, containing atomic and molecular emissions, can be used to differentiate between the two tissue types. The measurements and differentiation were performed in open air and under normal stray light conditions.
Keywords: laser induced breakdown spectroscopy; plasma; chemical composition; nerve; parotid-gland

Investigation of the differentiation of ex vivo nerve and fat tissues using laser-induced breakdown spectroscopy (LIBS): Prospects for tissue-specific laser surgery - Mehari, Fanuel; Rohde, Maximilian; Kanawade, Rajesh; Knipfer, Christian; Adler, Werner; Klämpfl, Florian; Stelzle, Florian; Schmidt, Michael (Journal of Biophotonics, 2016)
Keywords: Laser induced-breakdown spectroscopy; plasma; elements; laser surgery; fat-nerve

In Vivo Monitoring of Hemodynamic Changes during Clogging and Unclogging of Blood Supply for the Application of Clinical Shock Detection - Kanawade, Rajesh; Stelzle, Florian; Schmidt, Michael (Physics Procedia, 2012)

In-vivo multispectral Video Endoscopy towards in-vivo hyperspectral Video Endoscopy - Hohmann, Martin; Kanawade, Rajesh; Klämpfl, Florian; Douplik, Alexandre; Mudter, Jonas; Neurath, Markus; Albrecht, Heinz (Journal of Biophotonics, 2016)

Laser induced breakdown spectroscopy for bone and cartilage differentiation - ex vivo study as a prospect for a laser surgery feedback mechanism - Mehari, Fanuel; Rohde, Maximilian; Knipfer, Christian; Kanawade, Rajesh; Klämpfl, Florian; Adler, Werner; Stelzle, Florian; Schmidt, Michael (Biomedical Optics Express, 2014)
Laser surgery enables for very accurate, fast and clean modeling of tissue. The specific and controlled cutting and ablation of tissue, however, remains a central challenge in the field of clinical laser applications. The lack of information on what kind of tissue is being ablated at the bottom of the cut may lead to iatrogenic damage of structures that were meant to be preserved. One such example is the shaping or removal of diseased cartilaginous and bone tissue in the temporomandibular joint (TMJ). Diseases of the TMJ can induce deformation and perforation of the cartilaginous discus articularis, as well as alterations to the cartilaginous surface of the condyle or even the bone itself. This may result in restrictions of movement and pain. The aim of a surgical intervention ranges from specific ablation and shaping of diseased cartilage, bone or synovial tissues to extensive removal of TMJ structures. One approach to differentiate between these tissues is to use Laser Induced Breakdown Spectroscopy (LIBS). The ultimate goal is a LIBS guided feedback control system for surgical laser systems that enables real-time tissue identification for tissue specific ablation. In the presented study, the authors focused on the LIBS based differentiation between cartilage tissue and cortical bone tissue using an ex-vivo pig model.

Measurement of optical properties of pig esophagus by using a modified spectrometer set-up - Hohmann, Martin; Lengenfelder, Benjamin; Kanawade, Rajesh; Klämpfl, Florian; Douplik, Alexandre; Albrecht, Heinz (Journal of Biophotonics, 2017)

Novel method for early signs of clinical shock detection by monitoring blood capillary/vessel spatial pattern - Kanawade, Rajesh; Klämpfl, Florian; Riemann, Max; Knipfer, Christian; Tangermann-Gerk, Katja; Schmidt, Michael; Stelzle, Florian (Journal of Biophotonics, 2014)
The ability to monitor capillary/vessel spatial patterns and local blood volume fractions is critical in clinical shock detection and its prevention in Intensive Care Units (ICU). Although the causes of shock might be different, the basic abnormalities in pathophysiological changes are the same. To detect these changes, we have developed a novel method based on both spectrally and spatially resolved diffuse reflectance spectra. The preliminary study has shown that this method can monitor the spatial distribution of capillary/vessel spatial patterns through local blood volume fractions of reduced hemoglobin and oxyhemoglobin. This method can be used as a real-time and non-invasive tool for the monitoring of shock development and feedback on the therapeutic intervention.
EVALuna2:24355

Photoplethysmography (PPG) Sensor for Real-time Body Hemodynamics Monitoring - An Efficient, Robust and Simple Approach for Clinical Shock Diagnostics - Kanawade, Rajesh; Alhamwi, Nawras; Klämpfl, Florian; Riemann, Max; Knipfer, Christian; Schmidt, Michael; Stelzle, Florian (OSA trends in optics and photonics, 2014)
The goal of this study is to explore the feasibility of the PPG sensor for the clinical shock detection by measuring hemodynamic parameters.<br

Pilot study of laser induced breakdown spectroscopy for tissue differentiation by monitoring the plume created during laser surgery - An approach on a feedback Laser control mechanism - Kanawade, Rajesh; Mehari, Fanuel; Knipfer, Christian; Rohde, Maximilian; Tangermann-Gerk, Katja; Schmidt, Michael; Stelzle, Florian (Spectrochimica Acta Part B-Atomic Spectroscopy, 2013)
This study focuses on tissue differentiation using 'Laser Induced Breakdown Spectroscopy' (LIBS) by monitoring the plasma plume created during laser surgery processes. This technique is aimed at controlling a laser surgery feedback system in real time. An Excimer laser (Ar-F 193 nm) was used for the ablation of tissue samples. Fat, muscle, nerve and skin tissue samples of bisected ex-vivo pig heads were prepared as test objects for the ablation procedure. A single fiber was used to collect emissions and deliver them to a spectrometer. The obtained LIBS spectra in the measured emissions were analyzed to determine each tissue type according to their chemical composition. The elements found in the samples and their emission spectra were in agreement with those described in literature. The collected LIBS spectra were analyzed to differentiate the tissues using statistical data analysis: Principal Component Analysis (PCA), Linear Discriminant Analysis (LDA) and Receiver Operating Characteristics (ROC). The obtained preliminary results suggest a successful differentiation of the target tissues with high sensitivity and specificity. The main goal of this study was to qualitatively identify tissue types during laser ablation, which will provide a real time feedback mechanism for clinical Laser surgery applications to significantly improve the accuracy and safety of laser surgery procedures. © 2013 Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Chemical composition; Laser surgery feedback control; Plasma; Statistical method; Tissue differentiation

Pilot study of LIBS for tissue differentiation by monitoring the plume created during laser surgery - an approach on a feedback Laser control mechanism - Kanawade, Rajesh; Mehari, Fanuel; Knipfer, Christian; Rohde, Maximilian; Tangermann-Gerk, Katja; Schmidt, Michael; Stelzle, Florian (Spectrochimica Acta Part B-Atomic Spectroscopy, 2013)
<div class="abstract svAbstract " data-etype="ab" style="border: 0px; font-size: 16px; margin: 0px; padding: 0px; vertical-align: baseline; font-family: Arial, Helvetica, 'Lucida Sans Unicode', 'Microsoft Sans Serif', 'Segoe UI Symbol', STIXGeneral, 'Cambria Math', 'Arial Unicode MS', sans-serif; color: rgb(46, 46, 46); line-height: 23.68px;"> This study focuses on tissue differentiation using ‘Laser Induced Breakdown Spectroscopy’ (LIBS) by monitoring the plasma plume created during laser surgery processes. This technique is aimed at controlling a laser surgery feedback system in real time. An Excimer laser (Ar-F 193 nm) was used for the ablation of tissue samples. Fat, muscle, nerve and skin tissue samples of bisected ex-vivo pig heads were prepared as test objects for the ablation procedure. A single fiber was used to collect emissions and deliver them to a spectrometer. The obtained LIBS spectra in the measured emissions were analyzed to determine each tissue type according to their chemical composition. The elements found in the samples and their emission spectra were in agreement with those described in literature. The collected LIBS spectra were analyzed to differentiate the tissues using statistical data analysis: Principal Component Analysis (PCA), Linear Discriminant Analysis (LDA) and Receiver Operating Characteristics (ROC). The obtained preliminary results suggest a successful differentiation of the target tissues with high sensitivity and specificity. The main goal of this study was to qualitatively identify tissue types during laser ablation, which will provide a real time feedback mechanism for clinical Laser surgery applications to significantly improve the accuracy and safety of laser surgery procedures.

Preparation of a skin equivalent phantom with interior micron-scale vessel structures for optical imaging experiments - Chen, Chen; Klämpfl, Florian; Knipfer, Christian; Riemann, Max; Kanawade, Rajesh; Stelzle, Florian; Schmidt, Michael (Biomedical Optics Express, 2014)
A popular alternative of preparing multilayer or microfluidic chip based phantoms could have helped to simulate the subsurface vascular network, but brought inevitable problems. In this work, we describe the preparation method of a single layer skin equivalent tissue phantom containing interior vessel channels, which mimick the superficial microvascular structure. The fabrication method does not disturb the optical properties of the turbiding matrix material. The diameter of the channels reaches a value of 50 μm. The size, as well as the geometry of the generated vessel structures are investigated by using the SD-OCT system. Our preliminary results confirm that fabrication of such a phantom is achievable and reproducible. Prospectively, this phantom is used to calibrate the optical angiographic imaging approaches.
Keywords: Medical optics and biotechnology; Turbid media; Medical and biological imaging; Optical properties

Qualitative tissue differentiation by analysing the intensity ratios of atomic emission lines using laser induced breakdown spectroscopy (LIBS): prospects for a feedback mechanism for surgical laser systems - Kanawade, Rajesh; Mehari, Fanuel; Klämpfl, Florian; Rohde, Maximilian; Knipfer, Christian; Tangermann-Gerk, Katja; Adler, Werner; Schmidt, Michael; Stelzle, Florian (Journal of Biophotonics, 2013)
The research work presented in this paper focuses on qualitative tissue differentiation by monitoring the intensity ratios of atomic emissions using 'Laser Induced Breakdown Spectroscopy' (LIBS) on the plasma plume created during laser tissue ablation. The background of this study is to establish a real time feedback control mechanism for clinical laser surgery systems during the laser ablation process. Ex-vivo domestic pig tissue samples (muscle, fat, nerve and skin) were used in this experiment. Atomic emission intensity ratios were analyzed to find a characteristic spectral line for each tissue. The results showed characteristic elemental emission intensity ratios for the respective tissues. The spectral lines and intensity ratios of these specific elements varied among the different tissue types. The main goal of this study is to qualitatively and precisely identify different tissue types for tissue specific laser surgery. (© 2013 WILEY-VCH Verlag GmbH &Co. KGaA, Weinheim).
EVALuna2:5391
Keywords: Laser induced breakdown spectroscopy; plasma; chemical composition; chemical elements; tissue type; intensity ratio

Recovering the superficial microvascular pattern via diffuse reflection imaging: phantom validation - Chen, Chen; Klämpfl, Florian; Kanawade, Rajesh; Riemann, Max; Knipfer, Christian; Stelzle, Florian; Schmidt, Michael (Biomedical Engineering Online, 2015)
Background <p style="padding: 0px; margin: 0px 0px 1em; border: 0px; outline: 0px; font-size: 11px; font-family: Verdana, Arial, Helvetica, sans-serif; vertical-align: baseline; overflow: hidden; color: rgb(0, 0, 0); line-height: 17.6px;"> Diffuse reflection imaging could potentially be used to recover the superficial microvasculature under cutaneous tissue and the associated blood oxygenation status with a modified imaging resolution. The aim of this work is to deliver a new approach of local off-axis scanning diffuse reflection imaging, with the revisit of the modified Beer–Lambert Law (MBLL). Methods <p style="padding: 0px; margin: 0px 0px 1em; border: 0px; outline: 0px; font-size: 11px; font-family: Verdana, Arial, Helvetica, sans-serif; vertical-align: baseline; overflow: hidden; color: rgb(0, 0, 0); line-height: 17.6px;"> To validate this, the system is used to recover the micron-scale subsurface vessel structure interiorly embedded in a skin equivalent tissue phantom. This vessel structure is perfused with oxygenated meta-hemoglobin solution. Results <p style="padding: 0px; margin: 0px 0px 1em; border: 0px; outline: 0px; font-size: 11px; font-family: Verdana, Arial, Helvetica, sans-serif; vertical-align: baseline; overflow: hidden; color: rgb(0, 0, 0); line-height: 17.6px;"> Our preliminary results confirm that the thin vessel structure can be mapped into a 2-D planar image. The distributions of oxygenated hemoglobin concentration (<a href="http://www.biomedical-engineering-online.com/content/14/1/87/mathml/M1" style="padding: 0px; margin: 0px; border: 0px; outline: 0px; font-weight: inherit; font-style: inherit; font-family: inherit; vertical-align: baseline; color: rgb(51, 102, 153);" title="View MathML"><img alt="<a onClick="popup('http://www.biomedical-engineering-online.com/content/14/1/87/mathml/M1','MathML',630,470);return false;" target="_blank" data-cke-saved-href="http://www.biomedical-engineering-online.com/content/14/1/87/mathml/M1" href="http://www.biomedical-engineering-online.com/content/14/1/87/mathml/M1">View MathML" class="mathimg" src="http://www.biomedical-engineering-online.com/content/inline/s12938-015-0081-x-i1.gif" style="padding: 0px; margin: 0px; border: 0px; outline: 0px; font-weight: inherit; font-style: inherit; font-family: inherit; vertical-align: middle; float: none;" />) and deoxygenated hemoglobin concentration (<a href="http://www.biomedical-engineering-online.com/content/14/1/87/mathml/M2" style="padding: 0px; margin: 0px; border: 0px; outline: 0px; font-weight: inherit; font-style: inherit; font-family: inherit; vertical-align: baseline; color: rgb(51, 102, 153);" title="View MathML"><img alt="<a onClick="popup('http://www.biomedical-engineering-online.com/content/14/1/87/mathml/M2','MathML',630,470);return false;" target="_blank" data-cke-saved-href="http://www.biomedical-engineering-online.com/content/14/1/87/mathml/M2" href="http://www.biomedical-engineering-online.com/content/14/1/87/mathml/M2">View MathML" class="mathimg" src="http://www.biomedical-engineering-online.com/content/inline/s12938-015-0081-x-i2.gif" style="padding: 0px; margin: 0px; border: 0px; outline: 0px; font-weight: inherit; font-style: inherit; font-family: inherit; vertical-align: middle; float: none;" />) can be co-registerated through the MBLL upon the CW spectroscopy, the scattering issue is addressed in the reformed MBLL. The recovered pattern matches to the estimation from the simultaneous optical coherence tomography studies. Conclusions <p style="padding: 0px; margin: 0px 0px 1em; border: 0px; outline: 0px; font-size: 11px; font-family: Verdana, Arial, Helvetica, sans-serif; vertical-align: baseline; overflow: hidden; color: rgb(0, 0, 0); line-height: 17.6px;"> With further modification, this system may serve as the first prototype to investigate the superficial microvasculature in the expotential skin cancer loci, or a micro-lesion of vascular dermatosis.
Keywords: Diffuse reflection; Angiographic imaging; Cutaneous tissue phantom